1997
DOI: 10.4315/0362-028x-60.10.1265
|View full text |Cite
|
Sign up to set email alerts
|

Surveillance for Foodborne Disease Outbreaks—United States, 1988–1992

Abstract: Data collected by the CDC through a collaborative surveillance program for collection and periodic reporting of data concerning the occurrence and causes of foodborne disease outbreaks (FBDOs) are reviewed for the period from January 1988 through December 1992. An FBDO is defined as the occurrence of two or more cases of a similar illness resulting from the ingestion of a common food. Before 1992 only one case of intoxication by chemical or other nonbacterial toxin, marine toxin, or Clostridium botulinum toxin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
161
0
1

Year Published

1998
1998
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 249 publications
(172 citation statements)
references
References 0 publications
2
161
0
1
Order By: Relevance
“…Humans are usually infected through consumption of contaminated foods of animal origin (2). In human and animal cases it is an enteric disease of varying severity, usually involving diarrhea (4).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Humans are usually infected through consumption of contaminated foods of animal origin (2). In human and animal cases it is an enteric disease of varying severity, usually involving diarrhea (4).…”
Section: Introductionmentioning
confidence: 99%
“…This bacterium is broad host-spectrum, and can be isolated from a wide range of animal species, including birds and reptiles (4). The animals usually are healthy carriers, and contaminated food plays an important role in the epidemiology of salmonellosis.…”
Section: Introductionmentioning
confidence: 99%
“…outbreaks were due to contamination by food handlers (BEAN et al, 1997); thus, confirming the impact professionals have in spreading Staphylococcus. This suggested an inadequate handling of cheese at the sale markets or during grating as indicated in the present research.…”
Section: Resultsmentioning
confidence: 60%
“…Other authors 4,6,12 have already reported the presence of L. monocytogenes, Salmonella spp., Shigella spp., Aeromonas hydrophila and other pathogenic microorganisms on fresh fruit and vegetables as well as in the related MP refrigerated products. According to BEAN et al 3 , the number of documented outbreaks of human diseases associated to the consumption of raw and MP fruit and vegetables has considerably increased in recent decades. Outbreaks involving Salmonella and tomato, as well as Salmonella and cantaloupe have just been reported (Promed week 12-19 July).…”
Section: Introductionmentioning
confidence: 99%